Air Quality Measurement and Modeling - Sallis, Philip (IntechOpen, 2016)
Addressing the matter of air quality in a collection of focused scientific topic chapters is timely as a contribution to the international discussion and challenges of global warming and climate change. This book engages with the debate by considering some of the social, public health, economic and scientific issues that relate to the contribution made by airborne pollutants to the observable trending variances in weather, climate and atmospheric conditions. From a wide range of submissions for inclusion in the book, there are seven carefully selected chapters that individually relate to air sampling and analysis: the monitoring, measurement and modelling of air quality. The authors come from a range of academic and scientific disciplines, and each is internationally credited in his/her field. This book will appeal to scholars, to students and generally to those interested in the following contemporary thought in the matter of environment pollution, air quality and the issues of climate and atmosphere the world is facing today.